Paul's Letter to Philemon - Winter, Sara C. (New Testament studies, 1987)
The Pauline epistle known as Philemon is generally understood to be a letter written by Paul to a slaveowner on behalf of the runaway slave Onesimus requesting that the latter be allowed to return without penalty to the household in which he served. This article proposes a new interpretation of the letter that differs from the traditional in four major points: (1) the letter is written to a church, a congregation of which the individual addressed in the main body of the letter is a member; it is not a personal letter. (2) the slave Onesimus is with Paul in prison because he was sent there by the individual addressed in the main body of the letter (probably Archippus) on behalf of the Colossae church; Onesimus did not run away. (3) Paul writes to request that Onesimus be released from his obligations in Colossae in order that he might remain with Paul to work in the church in a Christian ministry. (4) Paul makes clear that Onesimus is no longer to be considered a slave within the Christian community, and separately suggests Onesimus be manumitted.